Realizing a Fair Investment Climate: The Role of KPPU’s Extraterritorial Authority in Competition Law Enforcement - Firmansyah, Satrio; Negara, Dharma Setiawan; Hardyansah , Rommy (Journal of Social Science Studies, 2023)
Enforcement of competition law in Indonesia faces major challenges with the increasing number of foreign companies operating in the domestic market. The application of extraterritorial authority by the Business Competition Supervisory Commission (KPPU) is crucial in dealing with violations committed by foreign companies. This article analyzes the application of KPPU’s extraterritorial authority in enforcing competition law in the domestic market, which may involve foreign companies that affect the Indonesian market. Based on a juridical normative study, existing regulations provide a basis for KPPU to enforce the law against foreign companies even though they do not operate domestically. This study also identifies challenges in the implementation of extraterritorial authority, such as difficulties in accessing information and limited coordination between countries. It is recommended that KPPU strengthen international cooperation and update existing regulations, especially related to the development of digital markets. Effective law enforcement against foreign companies will increase market transparency and promote fairer competition in Indonesia.